(untitled) (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2025)
The increasing electronics gadget market in Nigeria has increased competition between manufacturers and retailers. Nevertheless, there is little understanding of the factors that affect consumer purchase intentions in this particular region, especially in terms of product quality and consumer reviews. This study examined the effect of product quality and consumer reviews on purchase intention of electronic gadgets in North Central, Nigeria. A survey research design was employed, with a determined sample size was 463 respondents using Cochran's formula for unspecified populations, and purposive sampling technique was used to select participants. A self-administered five-point Likert scale questionnaire was used to collect data, and Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the data in a two-stage approach to examine the measurement and structural models. Both product quality and consumer reviews were found to have significant effects on purchase intention, and product quality had a greater effect. Based on the findings of the study, it is recommended that manufacturers and retailers of electronic gadgets in the North Central region of Nigeria should give a lot of attention to product quality as it has a great effect on consumer purchase intentions. Revising for durability, high performance, and good after-sales service will increase the consumer’s confidence and frequency of purchase. Furthermore, reviews made by consumers are important in purchase decisions although not as much as the product quality. Organizations should therefore encourage customers to provide feedback, be transparent with the management of reviews, and use influencer marketing to increase trust.